Model Pengembangan Dakwah Berbasis Budaya Lokal - Anif Arifani, Moch. (Jurnal Ilmu Dakwah, 2010)
Daâwah and local culture have tight relations. Each daâwah events always exist in interacts with its around. How is daâwah subject doing activity and how is daâwah object (madâu) behaving in daâwah event of course always bring and involve its culture background. Daâwah approach not only use culture as daâwah medium but also in knowing madâu strata. The religious leaders as daâwah agent in java have done spreading by culture approach such using culture medium, art, lyrics, unique fashion, and so on.